Harmonic Reduction in Variable Frequency Drives Using Active Power Filter - M. Tamilvani; K. Nithya; M. Srinivasan; S.U Prabha (Institute of Advanced Engineering and Science, 2014)
In this paper Voltage Source Inverter (VSI) is used to supply a variable frequency variable voltage to a three phase induction motor drive in a variable speed application. One important complication is that, Voltage Source Inverter (VSI) used in VFD causes non-sinusoidal output voltage and current due to presence of harmonics. Shunt active filter with VSI topology is proposed for current harmonic elimination. The current control scheme proposed for SAPF is Synchronous Reference Frame theory applied to SVPWM. The reference current can be calculated by using Reference Frame Transformation, reference current are transformed from a−b−c stationary frame to d−q rotating frame. In SVPWM technique, the Active Power Filter reference voltage is generated and desired Active Power Filter output voltage is generated by SVPWM. The analysis of simulation results are carried out in MATLAB/SIMULINK model.